Determinants of quality of life among older people in Thalawa divisional secretariat division, Anuradhapura district, Sri Lanka - Sarath, Rathnayake (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Attendance for non urgent case during the after office hours is high in the emergency department and this had lead to the introduction of extended hours service in the polyclinic. Currently there are no study done in Kuching to determine the reasons for these attendances in the emergency department and polyclinic. The objective of this study is to determine the reasons for seeking care during after-hours in the Mosque Road Polyclinic and the Emergency Department, Sarawak Geneal Hospital, Kuching. This study was conducted through a cross sectional study and the data were obtained through a self administered questionnaire. The respondents were obtained by convenient random sampling. The self administered questionnaire was developed based on the literature review.